2020
DOI: 10.3389/fimmu.2020.01415
|View full text |Cite
|
Sign up to set email alerts
|

Csf2 Attenuated Sepsis-Induced Acute Kidney Injury by Promoting Alternative Macrophage Transition

Abstract: Sepsis is a systemic inflammatory state that occurs in response to infection and significantly increases mortality in combination with acute kidney injury (AKI). Macrophages accumulate in the kidney after injury and undergo a transition from a proinflammatory (M1) phenotype to an alternatively activated (M2) phenotype that is required for normal repair. However, the specific signals that regulate the transition from the M1 to M2 phenotype in vivo are unknown. Here, we found an unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…1,2 As a terrible generalized hyperinflammatory condition, sepsis patients suffer a variety of tissue injuries and organ dysfunctions involving in lung, kidney, and heart. [3][4][5] Despite many efforts have been made to reduce mortality and improve the cure rate of sepsis worldwide, sepsis remains a terrible disease that seriously threatens the patients. Only 30% septic patients survive according to statistics, besides, at least 6 million patients die from septic infection annually according to the statistics of the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As a terrible generalized hyperinflammatory condition, sepsis patients suffer a variety of tissue injuries and organ dysfunctions involving in lung, kidney, and heart. [3][4][5] Despite many efforts have been made to reduce mortality and improve the cure rate of sepsis worldwide, sepsis remains a terrible disease that seriously threatens the patients. Only 30% septic patients survive according to statistics, besides, at least 6 million patients die from septic infection annually according to the statistics of the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…Canonical M2-associated genes CCL24 and CLEC4A (Makita et al, 2015;Tang et al, 2017) were also induced at 3 hours post-stimuli and reached peak expression around 6 hours ( Figure 1D Lower). M2 also showed higher expression of signaling molecule CSF2 that was recently shown to promote macrophages transition into an M2 phenotype (Li et al, 2020). Therefore, important expression changes leading to terminal polarization of macrophage subtypes were established within the first 6 hours following addition of stimuli.…”
Section: Distinct Subsets Of Genes Drive Macrophage Polarization Towamentioning
confidence: 85%
“…By analyzing microarray data from Spi-B-expressing A549 cells and control cells, we found that the expression of macrophage polarization-and recruitment-related genes, including CSF2, IL6, CCL3, and CCL4, was significantly upregulated by Spi-B. CSF2 is an important survival, proliferation, and differentiation factor for macrophages and neutrophils, and it promotes the infiltration of monocytes and macrophages into injured tissues (24)(25)(26). CSF2 also regulates the switch from the proinflammatory M1 phenotype to the M2 phenotype via the p-Stat5 pathway (24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…CSF2 is an important survival, proliferation, and differentiation factor for macrophages and neutrophils, and it promotes the infiltration of monocytes and macrophages into injured tissues (24)(25)(26). CSF2 also regulates the switch from the proinflammatory M1 phenotype to the M2 phenotype via the p-Stat5 pathway (24,26,27). IL6, a proinflammatory cytokine secreted by various cell types, plays several biological roles in different cells (28).…”
Section: Discussionmentioning
confidence: 99%